Civil Law in Practice Between Theory and Reality - I Gede Sujana; Anjelia Pendi Jola; Alexandrio Ngindi Ate; Patrisia Rambu Sedu (Journal of Multidisciplinary Law Studies, 2026)
Civil law is traditionally understood as a systematic and codified legal framework designed to ensure legal certainty, predictability, and coherence in regulating private legal relations. However, the practical application of civil law often reveals a significant gap between theoretical ideals and real-world implementation. This article aims to critically analyze the tension between civil law theory and its practice, focusing on how normative principles operate within judicial interpretation and social realities. This study employs a normative juridical research method with a qualitative and critical analytical approach. The analysis is based on secondary legal materials, including civil codes, judicial decisions, scholarly journal articles, and authoritative legal literature. Doctrinal, philosophical, and comparative approaches are used to examine the extent to which civil law theory aligns with or diverges from its practical application. The findings indicate that civil law in practice is not merely a mechanical application of codified norms. Instead, it is shaped by judicial discretion, interpretative flexibility, socio-economic change, and evolving societal values. The pursuit of legal certainty frequently encounters the demand for substantive justice, compelling judges to adopt purposive and contextual interpretations. Moreover, technological developments and globalization further challenge the adequacy of traditional civil law concepts. This article concludes that the gap between civil law theory and practice is structural rather than incidental. Bridging this gap requires reconceptualizing civil law theory to acknowledge interpretation, context, and justice as integral elements of legal practice. Such an approach allows civil law to remain normatively coherent while responsive to contemporary legal challenges.